2013
DOI: 10.1097/bor.0b013e3283620777
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and vertebral fractures in ankylosing spondylitis

Abstract: Osteoporosis is a common problem for patients with AS. We recommend screening within 10 years of diagnosis. Suspecting and promptly recognizing vertebral fractures in patients with AS could prevent serious neurological complications. Although bisphosphonates and tumor necrosis factor-α inhibitors look promising, further prospective trials on the treatment of osteoporosis in AS are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 37 publications
0
72
1
7
Order By: Relevance
“…[6,7] Cooper et al [6] identified markedly increased relative risk of vertebral morphometric deformities in patients with AS compared with the control population. The review of recent literature on osteoporosis and vertebral fractures in AS published by DaveyÀRanasinghe and Deodhar [8] suggests that the prevalence of osteoporosis in AS patients is 25% and that of vertebral fractures is 10%. Both new bone formation and vertebral osteoporosis with its consequences might contribute to spinal pain, stiffness, loss of mobility and functional impairment in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Cooper et al [6] identified markedly increased relative risk of vertebral morphometric deformities in patients with AS compared with the control population. The review of recent literature on osteoporosis and vertebral fractures in AS published by DaveyÀRanasinghe and Deodhar [8] suggests that the prevalence of osteoporosis in AS patients is 25% and that of vertebral fractures is 10%. Both new bone formation and vertebral osteoporosis with its consequences might contribute to spinal pain, stiffness, loss of mobility and functional impairment in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of Chinese AS patients are HLA-B27 positive, with the predominant subtype being HLA-B * 2704 (3). The axial spine and joints are most commonly affected in patients with AS; however, the disease also affects the heart, lungs, eyes, and colon, leading to complications such as uveitis (4), iridocyclitis (5), osteoporosis (6) and inflammatory bowel disease (7). Treatments for AS include non-steroidal anti-inflammatory drugs, tumor necrosis factor-alpha (TNF-α) inhibitors and physiotherapy to alleviate joint pain and stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of osteoporosis in individuals with AS is approximately 25% and vertebral fractures approximately 10%. Osteoporosis usually occurs after 10 years of AS disease 80 . Individuals with AS having a deficiency of vit D, have higher prevalence of osteoporosis instead of patients with normal status of 25(OH)D. Several studies have indicated the relative low status of 25(OH)D with the appearance of osteoporosis, and that vitamin D deficiency leads to osteoporosis through the promotion of inflammatory activity 62,64,81 .…”
Section: Vitamin D and Common Comorbidities In As Patientsmentioning
confidence: 99%
“…As mention patients with AS, frequently present increased rate of osteoporosis, poor quality of bones and vertebral fractures. Therefore, a screening of osteoporosis within a period of 10 years since the diagnosis is suggested and an assessment of the identified risk factors as well as the duration and activity of AS should also be considered 14,80 .…”
Section: Vitamin D and Common Comorbidities In As Patientsmentioning
confidence: 99%